Nephroprotective Effects of Celery Extract (Apium graveolens L.) on Unilateral Ureteral Obstruction Models - Shafira Audy Prameswari; Yoana Rizki Deviriandra; Ariadne Hapsari Putri Taufik; Rizky Aliyah Putri; Athaya Helia Untari; Afifah Afifah (GLOBAL HEALTH SCIENCE GROUP, 2026)
Renal fibrosis represents the final pathological endpoint of chronic kidney injury, characterized by excessive extracellular matrix deposition and irreversible structural damage, ultimately leading to end-stage kidney disease (ESKD) necessitating renal replacement therapy. Given the largely irreversible nature of established fibrosis, current therapeutic approaches primarily aim to suppress fibrogenesis and delay further renal deterioration. Celery (Apium graveolens L.) contains bioactive compounds with potential nephroprotective properties. Unilateral ureteral obstruction (UUO) is a well-established experimental model of renal fibrogenesis, in which persistent obstruction leads to tubular injury and activation of profibrotic signaling pathways. This study aimed to evaluate the nephroprotective effect of celery ethanol extract on renal injury in UUO rat model. A post-test-only control group design was conducted using 25 rats randomly assigned into five groups: sham control, negative control (UUO), and three treatment groups receiving celery extract (125, 250, and 500 mg/kg body weight) for 14 days. Serum creatinine levels were measured from blood samples, while renal tubular injury scores were assessed through histopathological examination of kidney tissues. One-way ANOVA followed by a least significant difference (LSD) post hoc test revealed significant differences among groups (p < 0.05), with the 250 mg/kg dose showing the most pronounced effect, suggesting potential nephroprotective activity. These findings necessitate further investigations, including toxicity assessment and clinical studies, to establish its therapeutic applicability.